Feedbacks: Financial Markets and Economic Activity - Brunnermeier, Markus; Palia, Darius; Sastry, Karthik A.; Sims, Christopher A. (American Economic Review, 2021)
Is credit expansion a sign of desirable financial deepening or the prelude to an inevitable bust? We study this question in modern US data using a structural VAR model of 10 monthly frequency variables, identified by heteroskedasticity. Negative reduced-form responses of output to credit growth are caused by endogenous monetary policy response to credit expansion shocks. On average, credit and output growth remain positively associated. “Financial stress” shocks to credit spreads cause declines in output and credit levels. Neither credit aggregates nor spreads provide much advance warning of the 2008–2009 crisis, but spreads improve within-crisis forecasts. (JEL C51, E23, E31, E43, E44, E52, G01)